Xylotrechus (Kostiniclytus) alakolensis sp. nov. (Coleoptera, Cerambycidae) from East Kazakhstan - Karpiński, Lech; Szczepański, Wojciech T. (Zootaxa, 2018)
Xylotrechus (Kostiniclytus) alakolensis sp. nov. from East Kazakhstan is described. Distinguishing characters from closely related species are presented and discussed. The habitus, male genitalia and habitat of the newly described species are illustrated. The new species differs from X. (K.) arnoldii mainly due to its denser pubescence, stockier body sculpture, shape of the scutellum and shorter metatarsomere 1. It can also easily be distinguished from X. (K.) medvedevi inter alia by its smaller eyes, sparser pubescence of the pronotum and elytra, shorter 3rd antennal joint and more elongate, acute lobes of the protarsomere 3. Moreover, there are distinct differences in the morphology of the male genitalia in both cases. Furthermore, the Kostiniclytus subgenus consists exclusively of allopatric representatives and the new described species is distributed about 1,000 km from the known localities of most of the related taxa.